-6|k+9|=-30

Divide each term in -6|k+9|=-30 by -6.

-6|k+9|-6=-30-6

Cancel the common factor of -6.

Cancel the common factor.

-6|k+9|-6=-30-6

Divide |k+9| by 1.

|k+9|=-30-6

|k+9|=-30-6

Divide -30 by -6.

|k+9|=5

|k+9|=5

Remove the absolute value term. This creates a ± on the right side of the equation because |x|=±x.

k+9=±5

Set up the positive portion of the ± solution.

k+9=5

Subtract 9 from both sides of the equation.

k=5-9

Subtract 9 from 5.

k=-4

k=-4

Set up the negative portion of the ± solution.

k+9=-5

Subtract 9 from both sides of the equation.

k=-5-9

Subtract 9 from -5.

k=-14

k=-14

The solution to the equation includes both the positive and negative portions of the solution.

k=-4,-14

Solve for k -6|k+9|=-30